Assessment on interface slip of steel-concrete-steel sandwich panels with ribbed bar connectors. (April 2023) - Yan, Meng; Wang, Lian-guang; Chen, Bai-ling; Zhang, Yao-sheng
Abstract: Steel-concrete-steel (SCS) sandwich structure is widely used because of its excellent mechanical properties. A SCS sandwich panel with ribbed bar connectors (B-SCS) was developed. Experiments were carried out on seven specimens where the faceplate thickness, loading mode, connectors spacing and connector type were varied. Test results reported the failure mode and crack distribution of the B-SCS structure. The bearing capacity of the structure with the ribbed bars was 36% higher than that with studs (the length is 60 mm). At the same time, the bottom faceplate determined the resistance limit and ductility of the B-SCS sandwich panel. The proposed interface slip model can accurately predict the relative displacement between the steel plate and the concrete. Under the peak load, the sliding amount of the top plate was less than 12% of that of the bottom plate. Highlights: A steel-concrete-steel (SCS) sandwich panel with ribbed bar connectors (B-SCS) is developed, the bearing capacity of it is 36% higher than the SCS panel with headed studs. The failure mechanism, crack distribution and load-displacement curves of the B-SCS structure are discussed. The steel plate thickness, loading mode, spacing of connectors and connector type parameters are studied parametrically. A prediction model of interface slip between steel plate and concrete is proposed and verified accurately.